Individual responsibility and climate action: some lessons from a perception survey administered in Hauts-de-France. Issue 1 (2nd January 2021) - Frère, Séverine; Marega, Oumar; Hellequin, Anne-Peggy; Flanquart, Hervé; Calvo-Mendieta, Iratxe; Berry, Baptiste; Cornet, Sophie
ABSTRACT: Given the public's limited concern about climate change, it is hard to imagine individual climate action. In recent decades, environmental policies in France have focused on a citizen accountability approach that encourages "virtuous behaviour". But this may not be adequate. Results from a 2017 perception survey conducted in the Hauts-de-France region show that this approach is not reaching its objectives among those who are financially less secure and mistrustful of authorities. This population is delegating responsibility to collective actors. In Lille and Chauny it appears that there can be no long-term projection of actions to combat climate change because everyday needs are more important. Individual and collective actions need to be balanced and part of the same dynamic. The disengagement of the welfare state does not favour this balance.